Safety profile of sikamat virus and its oncolytic potential in leukemic cells and cancer stem cells - Siew, Zhen Yun; Ong, Ghee Khang; Wong, Siew Tung; Leong, Pooi Pooi; Tan, Boon Shing; Leong, Chee-Onn; Chupri, Juita; Fang, Chee-Mun; Voon, Kenny (Nature Research, 2025)
Leukaemia remains a global health concern. The oncotherapy resistance of leukaemia might be due to the existence of cancer stem cell populations. This study investigated the therapeutic potential of Sikamat virus (PRV7S), a Pteropine orthoreovirus, as an oncolytic virus against acute myeloid leukaemia (AML) and chronic myeloid leukaemia (CML). Using AML and CML cell lines (THP-1 and K562), as well as an AML-M5-derived cancer stem cell (CSC) model, PRV7S was shown to infect these leukaemic cells, replicate within them, and reduce their viability. PRV7S-induced cell death was associated with caspase-mediated apoptosis without significant cell cycle arrest. Transcriptomic and proteomic analyses revealed that PRV7S infection altered several cell death pathways, including apoptosis and necroptosis, highlighting its complex cell death mechanisms. PRV7S replicated efficiently in infected cells, though it did not cause persistent infection. An in vivo safety evaluation in immunocompetent mice demonstrated that PRV7S was well-tolerated, showing no adverse effects on survival, body weight, or histopathology, and no evidence of viral persistence. These findings suggest PRV7S as a promising oncolytic candidate for myeloid leukaemia, with potential efficacy against CSCs and a favourable safety profile. In conclusion, the study provides new insights into the cellular pathways involved in PRV7S-mediated oncolysis and supports further exploration of PRV7S’s potential against resistant leukaemic and solid tumours.